2016
DOI: 10.1002/2327-6924.12352
|View full text |Cite
|
Sign up to set email alerts
|

What are we missing? Risk behaviors among Arab‐American adolescents and emerging adults

Abstract: Background and purpose Research on Arab‐Americans as a distinct ethnic group is limited, especially when considering the health of Arab‐American youth. This study describes health risk (substance use, violence); health promotive behaviors (hope, spirituality); and sexual activity (oral, vaginal, anal sex) of Arab‐American adolescents and emerging adults (aged 15–23) within their life context, as well as the association between these behaviors. Methods A secondary analysis of data on a subset of Arab‐American p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Adolescents experienced a great deal of discrimination from teachers, school administrators, and their classmates suggesting the need for more dedicated research on how discrimination impacts adolescents ( 128 ). A recent analysis by Munro-Kramer et al found two distinct subgroups of Arab American adolescents in their sample from the Midwest: those with multiple high risk behaviors and those with minimal risk behaviors and more positive life experiences ( 129 ). This analysis of high risk behaviors like sexual activity, tobacco use, and physical activity provides a perspective on the potential health needs of Arab American adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents experienced a great deal of discrimination from teachers, school administrators, and their classmates suggesting the need for more dedicated research on how discrimination impacts adolescents ( 128 ). A recent analysis by Munro-Kramer et al found two distinct subgroups of Arab American adolescents in their sample from the Midwest: those with multiple high risk behaviors and those with minimal risk behaviors and more positive life experiences ( 129 ). This analysis of high risk behaviors like sexual activity, tobacco use, and physical activity provides a perspective on the potential health needs of Arab American adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…More recent research has shown that sexual attitudes of Arab American young adults lean toward permissiveness with some traditional norms reflected through sexual double standards (e.g., men are allowed to have premarital sex while women are not). However, and contrary to societal expectations, Arab American young adults are in fact engaging in sex outside of marriage or same-sex relationships but are not accessing adequate sexual health promotion resources or education, which place them at risk for adverse sexual health outcomes (Abboud et al, 2020;Munro-Kramer et al, 2016). Therefore, there is a need to understand the unique realities faced by this young population, including the familial influences to develop tailored sexual health promotion programs.…”
Section: Sexuality Among Arab American Young Adultsmentioning
confidence: 97%
“…Additionally, 'there is a growing international recognition that modern adolescence extends into the early 20s' (25). Given the overlap and fluidity between the two age groups, research with young people has expanded to include a wider range of youth, particularly those aged 16 to 25 (5,14,(26)(27)(28). Given this fluidity, the research team decided to recruit emerging adults enrolled in a university health science program to participate in the study.…”
Section: Setting and Samplementioning
confidence: 99%
“…Additionally, alcohol consumption is common for Ugandan adolescents and subsequently linked to other behaviors that can impact health including sexual risk behaviors (7,8). Seeley et al (9) found that being young (age [13][14][15][16][17][18][19][20][21][22][23][24] and participating in other risky behaviors (alcohol use, cigarette smoking) was associated with increased prevalence of HIV infection in Uganda.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation